Pulpotomy: A journey through the products available over time - Souza, Rogério Emílio de (Seven Editora, 2024)
The objective of this chapter is to present two preventive techniques of pulp therapy, with a view to avoiding pulpectomy, and to explain the medications used in such procedures. DOI:https://doi.org/10.56238/sevened2023.007-091